Organic Reactions 2019
DOI: 10.1002/0471264180.or100.14
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Amination of Aryl Halides

Abstract: Palladium‐catalyzed amination of aryl halides is widely used in the synthesis of N ‐aryl amine derivatives. N ‐Aryl amines have important applications as pharmaceuticals, agricultural chemicals, and electronic materials. This chapter provides a summary of the mechanism, the optimal choice of catalyst, and the scope of this important reaction. Application to the arylation of ammonia, amines, amide derivatives, hydrazines, NH imines, and azoles are discussed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 264 publications
1
27
0
Order By: Relevance
“…The negative charge on the nitrogen is directly correlated to the rate of the elimination reduction (Figure 5). [46] Figure 1. Highly used drugs with N-heterocyclic core.…”
Section: Buchwald-hartwig Aminationmentioning
confidence: 99%
“…The negative charge on the nitrogen is directly correlated to the rate of the elimination reduction (Figure 5). [46] Figure 1. Highly used drugs with N-heterocyclic core.…”
Section: Buchwald-hartwig Aminationmentioning
confidence: 99%
“…Most examples of such couplings have been reported with different palladium catalytic systems and aryl halides as coupling partners at higher reaction temperatures . Hartwig et al, , Shaughnessy et al, and a few others have reported ambient-temperature protocols for the above transformation; however, chloroheteroarenes as coupling partners have seldom performed at such low temperatures. The catalytic efficiency of the Cu­(II)/PTABS system was therefore tested for a range of primary alkyl amines at ambient temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of adamantane-containing 4,6-diaminopyrimidines was studied using a model compound 5a with Pd(dba) 2 as a precatalyst (Scheme 4, Table 1). Classical phosphine ligands, like BINAP (2,2 -bis(diphenylphosphino)-1,1 -binaphthyl) and DavePhos (2-Dicyclohexylphosphino-2 -(N,N-dimethylamino)biphenyl) [35], were studied, as well as Ph-JosiPhos and Cy-JosiPhos (CyPF-t Bu), which were shown to be efficient in the amination of halosubstituted heterocycles [36,37], were also tested. Other donor phosphine ligands with bulky substituents (SPhos, XPhos, RuPhos BrettPhos) were not studied in this reaction as they earlier had been shown to be much less efficient in the heteroarylation of adamantane-containing amines with 2-bromopyridines [38].…”
Section: Resultsmentioning
confidence: 99%